Perfil hematológico en adolescentes embarazadas con complicaciones obstétricas atendidas en el Hospital Provincial Docente de Riobamba. - Castillo Jiménez, María Belén (2025)
Adolescent pregnancy entails a great challenge in the field of maternal and child health, due to the vulnerability of presenting alterations during the gestation period. These alterations are associated with changes in the hematological profile, underscoring the need for continuous monitoring to prevent an increase in obstetric complications in the study population of pregnant women. The main objective was to interpret the hematological profile results in pregnant adolescents with obstetric complications treated at the Provincial General Teaching Hospital of Riobamba. The research used a descriptive, quantitative approach in a non-experimental field, with a transversal and retrospective design. The study population comprised 120 medical records of pregnant adolescents treated at the Provincial Teaching Hospital of Riobamba between January and December 2021, of which 97 were selected for the project, providing key information for its development. The study showed that the main obstetric complications are, first, anemia: 40% in the first trimester, 45% in the second, and 43% in the third. Blood count was one of the most requested tests, in anemia with 34%, urinary infections with 32% and in the threat of preterm labor with 29%. Regarding hematological parameters, all complications were more prevalent in hematocrit, hemoglobin, neutrophils, and lymphocytes. These results highlight the need for laboratory tests during gestation to prevent obstetric complications.